HUBUNGAN KEPEMIMPINAN MANAJER DENGAN KEPUASAN KERJA KARYAWAN DI SOFYANINNHOTEL RANGKAYO BASA PADANG - Novita Sari, Dwi Putri; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The purpose of research is to examine the relationship between the leadership of managers with employee satisfaction in SofyanInn Hotel Rangkayo Basa Padang. This research is a correlational study involving two variables, namely on the leadership of managers and employee satisfaction. Population of this research are about 32 people that all employees except the manager. The sampling technique is non-probability sampling, by using saturated sampling, data collection technique is done by distributing questionnaires (questionnaire) as many as 52 items using the Likert scale that has been tested for validity and reliability. These results indicate that the majority of employees (68.7%) satisfaction of employees workingand (70 %) for leadership of the manager shows theunfavorableÂ category.The results also indicate that the presence of a positive and significant relationship between the variables X and Y with value corelation (r) of 0,634.